Influence of Tidal Trap Net (Belat) Shape Formation on Catches in The Village Anak Setatah District of West Rangsang Meranti Islands Regency of Riau Province - Nasution, Ramahan Tinggi; Brown, Arthur; Sari, T. Ersti Yulika (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of this study was to determine which catches most of the second form of splint. Consists of two forms of martial arts that is a rectangular shape and form of U. The results showed that the fishing gear rectangular shape overall number of catches is 57.10 kg consisted of 13 541 fish, while the U-shaped gear was brought 44.70 kg sand 9313 fishes.Results of t-test at 95% confidence level showed no difference in the two formations of the catch nets splint. Waters environmental conditions as long as the study were measured namely the highest tides reach 300-400 cm while the lowest ebbcurrent velocity reaches 30-40 cm, flow velocityis in the range of 10-15 cm/sec, temperatures ranging from 25-29 0C, salinity ranges from 35-40 0/00 and brightness ranges from 20-25 cm.Keywords: Tidal trap net, form of splint